Lung CT imaging in patients with bronchopulmonary dysplasia: A systematic review. Issue 9 (5th May 2016) - van Mastrigt, Esther; Logie, Karla; Ciet, Pierluigi; Reiss, Irwin K.M.; Duijts, Liesbeth; Pijnenburg, Mariëlle W.; Tiddens, Harm A.W.M.
Summary: Background: Bronchopulmonary dysplasia (BPD) is a common respiratory complication of preterm birth and associated with long‐term respiratory sequelae. Chest computed tomography (CT) is a sensitive tool to obtain insight in structural lung abnormalities and may be a predictor for later symptoms. Objectives: To give an overview of chest CT scoring methods that are used to evaluate chest CT scans of BPD patients. To review which structural lung abnormalities are described in children and adults with BPD and whether these are related to clinical outcomes. Methods: An extensive literature search was conducted for relevant studies on chest CT imaging in patients born preterm with BPD. Results: We retrieved 316 original papers of which 16 articles and three abstracts fulfilled our inclusion criteria. Overall, we identified nine different semi‐quantitative scoring methods. Chest CT scans revealed structural abnormalities in >85% of BPD patients. These abnormalities are decreased pulmonary attenuation, opacities, bronchial wall thickening, and consolidations. Some have been found to be negatively correlated with lung function and respiratory symptoms. Conclusions: None of the currently described scoring systems are appropriately validated or superior over another. Future studies are needed to generate a validated and universal chest CT quantitative scoring method for patients with BPD.Pediatr Pulmonol. 2016; 51:975–986 . © 2016 Wiley Periodicals, Inc.